Ag-modified polydopamine composite silk fibroin nanospheres Ag@SF@PDA and preparation method and application thereof

Ag modified nanospheres of polydopamine-complexed silk fibroin Ag@SF@PDA, which solves the problems of bacterial resistance and limited antibacterial effects caused by existing antibacterial materials, and achieves efficient bactericidal effects and wide application potential.

CN118109047BActive Publication Date: 2025-02-07GUANGDONG PHARMA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410093473.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2025-02-07
Estimated Expiration
2044-01-23

AI Technical Summary

Technical Problem

Existing antibacterial materials are prone to bacterial resistance during the bactericidal process, and polydopamine (PDA) has limited antibacterial effects and limited application range.

Method used

Ag is used to modify the nanosphere Ag@SF@PDA of polydopamine-complexed silk fibroin. It is modified on the surface of SF@PDA by PDA as the core, Silk fibroin (SF) as the shell, and silver ions (Ag) under the reduction of DA , form a composite nanosphere with a multi-layer structure.

Benefits of technology

Ag@SF@PDA has photothermal conversion performance and synergistic antibacterial properties, can effectively sterilize, with a sterilization rate of more than 95%, and is not easy to lead to bacterial resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118109047B_ABST
    Figure CN118109047B_ABST
Patent Text Reader

Abstract

The present invention discloses a nanosphere Ag@SF@PDA of Ag-modified polydopamine composite silk fibroin, and a preparation method and application thereof. The Ag@SF@PDA nanosphere of the present invention has a multilayer structure, with PDA as the core, SF as the shell, and Ag modified on the surface of SF@PDA. The preparation conditions of the Ag@SF@PDA of the present invention are mild and simple, and the requirements for equipment and environment are low. Ag@SF@PDA is nanoscale and is suitable for various surfaces, such as regular and irregular surfaces, and is also suitable for different fields, such as dressings, preservation, tissue repair, daily cosmetics, and medical fields. It has been verified that the Ag@SF@PDA of the present invention has photothermal conversion performance and synergistic antibacterial performance, and can effectively kill bacteria with a sterilization rate of more than 95%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new materials, and in particular relates to a Ag-modified polydopamine composite silk fibroin nanosphere Ag@SF@PDA and a preparation method and application thereof. Background Art

[0002] Bacteria easily adhere to the surface of various objects, such as food, medical equipment, daily necessities, etc., causing unpredictable consequences and losses. In addition, bacteria spread through the esophagus, respiratory tract and wounds into the human body, causing various bacterial infections, causing economic burdens, reduced quality of life and social problems. Therefore, the development of new materials with antibacterial functions has important economic and social benefits.

[0003] There are many kinds of antibacterial drugs at present, but they can easily make bacteria resistant. In the field of materials, the preparation of antibacterial materials is mainly to kill bacteria by adding antibacterial ingredients. Antibacterial ingredients are a class of substances with antibacterial and bactericidal properties, and are the core of antibacterial materials. Antibacterial ingredients can be roughly divided into organic low molecular weight, organic high molecular weight, natural extract antibacterial agents and composite antibacterial ingredients. Among them, dopamine (DA) is the main component of natural melanin in the human body. It not only has good in vivo degradation performance and non-toxicity, but also under alkaline conditions, DA can self-polymerize and adhere to the surface of the material to form a polydopamine (PDA) layer. PDA has excellent photothermal conversion ability, which enables it to convert light energy into heat energy under near-infrared laser irradiation, thereby playing an antibacterial role. This antibacterial method that relies on photothermal conversion will not cause bacteria to develop drug resistance. A Chinese patent application with publication number CN106800375A discloses a method for preparing a TiO2-modified dopamine antibacterial coating, wherein a solid material substrate is used, dopamine is self-polymerized on its surface, and then modified with TiO2 to synthesize a coating with antibacterial properties.

[0004] Silk fibroin (SF) is a natural polymer protein with good hydrophilicity and excellent biocompatibility. The composite of PDA and SF has been used in many fields, such as dressings, tissue engineering and medical textiles, and has achieved good results. In specific applications, PDA and SF exist in the form of membranes, fibers or hydrogels, and even the two are only used to modify the surface of other materials. PDA and SF composite nanospheres are rarely reported. In addition, the antibacterial effect of PDA is relatively weak, and the range of antibacterial species is relatively small. When it is combined with Ag, a metal material with spectral antibacterial properties, it will produce a combined antibacterial effect. The composite of PDA, SF and Ag at the nanoscale can expand the types and application range of functional materials. Summary of the invention

[0005] The technical problem to be solved by the present invention is to propose a Ag-modified polydopamine composite silk protein nanosphere Ag@SF@PDA and its preparation method and application. The Ag-modified polydopamine composite silk protein nanosphere Ag@SF@PDA of the present invention has a multilayer structure, with PDA as the core and SF as the shell. Ag is modified on the surface of SF@PDA to form a relatively stable complex. SF in Ag@SF@PDA can be replaced by other biocompatible proteins or polysaccharides, such as collagen, chitosan, gelatin, sodium alginate, etc.

[0006] The preparation method of the present invention comprises the following steps:

[0007] S1. Preparation of SF@PDA nanospheres

[0008] Prepare SF aqueous solution, adjust the pH value to 7, disperse PDA nanospheres in the SF solution, stir and react at room temperature, then ultrasonically clean and centrifuge, and dry in low temperature vacuum to obtain SF@PDA nanospheres;

[0009] S2. Preparation of Ag@SF@PDA nanospheres

[0010] Silver nitrate solution and DA Tris-HCl solution were prepared, SF@PDA nanospheres were dispersed in DA Tris-HCl solution for reaction, and then silver nitrate solution was added dropwise with stirring. After the reduction reaction, they were first ultrasonically cleaned in deionized water, rinsed with deionized water, ultrasonically cleaned in ethanol, and then centrifuged and vacuum dried at room temperature to obtain Ag@SF@PDA nanospheres.

[0011] The preparation conditions of the Ag@SF@PDA of the present invention are mild and simple, and the requirements on equipment and environment are relatively low.

[0012] The Ag@SF@PDA of the present invention is nanoscale and is applicable to various surfaces, such as regular and irregular surfaces, and is also applicable to different fields, such as dressings, antisepsis, tissue repair, daily cosmetics, and medical treatment.

[0013] It has been verified that the Ag@SF@PDA of the present invention has photothermal conversion performance and synergistic antibacterial performance, and can effectively kill bacteria with a sterilization rate of more than 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 FE-SEM images of the nanospheres: A: PDA; B: SF@PDA; C: Ag@SF@PDA;

[0015] Figure 2FE-SEM images, element content table and element spectrum of SF@PDA and Ag@SF@PDA; A1-A3 are FE-SEM images, element content table and element spectrum of SF@PDA; B1-B3 are FE-SEM images, element content table and element spectrum of Ag@SF@PDA;

[0016] Figure 3 A is the silver element distribution diagram and the distribution state diagram of nanoparticles in the FE-SEM image; A is the FE-SEM image of Ag@SF@PDA; BC are the distribution energy spectra of Ag, C and O elements respectively;

[0017] Figure 4 Temperature change spectrum of each sample after 10 min of near-infrared light irradiation: A: DA solution, B: SF / DA solution, C: SF / DA / AgNO3 solution, D: PDA, E: SF@PDA, F: Ag@SF@PDA;

[0018] Figure 5 Antibacterial graphs of blank, DA solution, SF / DA solution, and SF / DA / AgNO3 solution;

[0019] Figure 6 The antibacterial graphs of blank and DA solution, SF / DA solution, and SF / DA / AgNO3 solution were irradiated with near infrared for 10 min;

[0020] Figure 7 The antibacterial profiles of blank, PDA, SF@PDA, and Ag@SF@PDA;

[0021] Figure 8 The antibacterial spectra of blank, PDA, SF@PDA, and Ag@SF@PDA were obtained after near-infrared irradiation for 10 min. DETAILED DESCRIPTION

[0022] In order to allow those skilled in the art to understand the present invention more clearly and intuitively, the present invention will be further described below in conjunction with the accompanying drawings.

[0023] The technical solution of the present invention is to prepare Ag@SF@PDA nanospheres with a multilayer structure, PDA as the core, SF as the shell, and Ag ions are reduced by DA to Ag modified on the surface of SF@PDA. In addition, as an alternative, SF in Ag@SF@PDA in the present invention can be replaced by other biocompatible proteins or polysaccharides, such as collagen, chitosan, gelatin, sodium alginate, etc.

[0024] Preparation of Ag@SF@PDA nanospheres

[0025] 1. Sample preparation

[0026] 1. SF Extraction and PDA Nanosphere Preparation

[0027] Preferred solution: Prepare a Na2CO3 solution with a mass concentration of 0.5 mg / mL, heat the Na2CO3 solution to boiling, add an appropriate amount of silk, boil for 30 minutes, repeat three times, and dry in an oven at 45°C overnight. Prepare a CaCl2-CH3CH2OH-H2O three-phase solution with a molar ratio of 1:2:8 with ultrapure water and heat it. After the dried silk is completely dissolved and cooled to room temperature, it is dialyzed with ultrapure water and placed in a dialysis bag for three days, during which the water is changed every 4 hours. Filter the dialysate and place it in a freeze dryer for freeze drying for 24 hours, then take it out and place it in a drying oven for later use. Dissolve DA in Tris-HCl solution to prepare a solution with pH=8 and a mass concentration of 50 mg / mL, then add it to a CH3CH2OH-H2O solution with a volume ratio of 9:4 and stir rapidly at room temperature for 18h to 24h. After centrifugation (10000rpm, 15min), the precipitate obtained is washed three times with ethanol and distilled water respectively, and freeze-dried for use.

[0028] Alternative solution: Prepare a Na2CO3 solution with a mass concentration of 0.5%, and add an appropriate amount of silk after heating the Na2CO3 solution to boiling, boil for 30 minutes, repeat three times, and dry in an oven at 45°C overnight. Prepare a CaCl2-CH3CH2OH-H2O three-phase solution with a molar ratio of 1:2:8 with ultrapure water and heat it. After the dried silk is completely dissolved and cooled to room temperature, it is dialyzed with ultrapure water and placed in a dialysis bag for three days, during which the water is changed every 4 hours. Filter the dialysate and place it in a freeze dryer for freeze drying for 24 hours, then take it out and place it in a drying oven for later use. Dissolve DA in Tris-HCl solution to make a solution with a pH of 8 and a mass concentration of 25 mg / mL, add it to a CH3CH2OH-H2O solution with a volume ratio of 9:4, and stir rapidly at room temperature for 18h to 24h. After centrifugation (10000rpm, 15min), the precipitate obtained is washed three times with ethanol and distilled water, and freeze-dried for use.

[0029] 2. Preparation of SF@PDA nanospheres

[0030] Preferred solution: Prepare 10 mL of 0.6 mg / mL SF solution and adjust the pH value to 7. Take 1 mg of PDA nanospheres, add 250 μL of water, mix and add to the SF solution, and stir at room temperature for 2 to 3 hours. After the reaction is completed, first ultrasonically clean for 5 minutes, three times, and then centrifuge several times to obtain a solid, namely SF@PDA nanospheres, and vacuum dry at low temperature.

[0031] Alternative solution: Prepare 10 mL of 1 mg / mL SF solution and adjust the pH value to 7. Take 1 mg of PDA nanospheres, add 250 μL of water, mix and add to the SF solution, and stir at room temperature for 4 to 6 hours. After the reaction is completed, ultrasonic cleaning is performed for 10 minutes, three times, and then centrifuged several times to obtain a solid, that is, SF@PDA nanospheres, which are vacuum dried at low temperature.

[0032] 3. Preparation of Ag@SF@PDA nanospheres

[0033] Preferred solution: Prepare silver nitrate solution with a concentration of 10 mg / mL and DA Tris-HCl solution with a concentration of 10 mg / mL respectively. First, add 2 mg of SF@PDA nanospheres to 30 mL of DA Tris-HCl solution for reaction for 2 hours, then add 5 mL of silver nitrate solution and stir slowly for reduction reaction for 1 hour until precipitation and suspended particles appear and stop the reaction. After the reaction, ultrasonic cleaning is performed in deionized water for 15 minutes, and repeated three times. Take out the reacted sample, rinse with deionized water, and then ultrasonicate in ethanol for 10 minutes. After three times, centrifuge and vacuum dry at room temperature to obtain Ag@SF@PDA nanospheres.

[0034] Alternative solution: Prepare 5mg / mL silver nitrate solution and 5mg / mL DA Tris-HCl solution respectively. First, add 3mg of SF@PDA nanospheres to 30mL DA Tris-HCl solution for 2h, then add 5mL of silver nitrate solution and stir slowly for 1h to reduce the reaction. When the suspended particles precipitate, stop the reaction. After the reaction, ultrasonically clean it in deionized water for 15min, and repeat three times. Take out the reacted sample, rinse it with deionized water, and then ultrasonicate it in ethanol for 10min. After three times, centrifuge it and vacuum dry it at room temperature to obtain Ag@SF@PDA nanospheres.

[0035] 2. Test Method

[0036] Shape detection

[0037] The Ag@SF@PDA nanosphere samples of each group were dropped onto aluminum foil, fixed to the stage with conductive glue after drying, sprayed with platinum for 100s, and observed and photographed with a field emission scanning electron microscope (FE-SEM) (JEOL Ltd., JSM-7610F PLUS), with a reference voltage of 15.0 kV and a working distance of 8.0 mm, and the diameter was tested with Image J software. The samples were analyzed for elements with the help of a surface energy spectrometer (Oxford Instruments, Ultim Max40).

[0038] Component detection

[0039] The molecular structure changes between the components of the sample were analyzed by infrared spectrometer (ThermoFisher, Nicolet iS50). The sample was prepared by tableting method and placed in the spectrometer for measurement with a scanning range of 500 cm -1 -4000cm -1 .

[0040] Photothermal detection

[0041] The samples were irradiated with 808 nm near-infrared laser (2.4 W) for 10 min. An infrared thermal imager (HIKVISION, China) was used to record the photothermal image and temperature change of the bacterial solution and sample mixture under near-infrared laser irradiation, and the highest temperature was recorded.

[0042] Antibacterial effect test

[0043] Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli were selected as representative test bacteria. The bacterial strains were cultured at 37°C for 12 h. The bacteria were then collected by centrifugation and washed three times with PBS. The resulting bacteria were redispersed in PBS solution and the bacterial concentration was adjusted by an ELISA instrument so that the bacterial solution concentration was approximately 10 6 CFU / mL. All samples and instruments were sterilized by UV or high temperature steam.

[0044] 100 μL of each sample with a concentration of 3 mg / mL was added to the sterilized sample bottle, and then 100 μL of bacterial solution was directly added to the sample. The blank group was the culture medium without sample. After the above groups were cultured at 37°C for 24 hours, photos were taken and recorded.

[0045] 100 μL of each sample with a concentration of 3 mg / mL was added to the sterilized sample bottle, and then 100 μL of bacterial solution was directly added to the sample, irradiated with near infrared (1.2V, 0.2A) for 10 minutes, and then cultured at 37°C for 24 hours, and photographed. The blank group was the culture medium without sample, irradiated with near infrared (1.2V, 0.2A) for 10 minutes, and then cultured at 37°C for 24 hours, and photographed.

[0046] 3. Results

[0047] Morphology characterization results (taking the preferred solution as an example)

[0048] like Figure 1 As shown in Figure 2, we successfully prepared PDA, SF@PDA and Ag@SF@PDA nanospheres. Each sample is generally spherical, with some nipple-like protrusions on PDA ( Figure 1 A), while the surface of SF@PDA formed by the adsorption of SF on the outer layer of PDA becomes smooth ( Figure 1B); After Ag modification, the nipple-like protrusions on the surface of the Ag@SF@PDA sample become more numerous and obvious than those on the PDA surface.

[0049] Element detection results

[0050] like Figure 2 As shown, the element spectrum of SF@PDA ( Figure 2 A3) and content table ( Figure 2 A2) No silver element was observed; the element spectrum of Ag@SF@PDA showed obvious Ag element peaks ( Figure 2 B3), its content is about 19.6wt% ( Figure 2 B2). The above results confirmed that silver was successfully modified on SF@PDA nanospheres.

[0051] like Figure 3 As shown in the figure, the silver element distribution diagram ( Figure 3 B) and FE-SEM images ( Figure 3 A) corresponds to the distribution of nanoparticles, further proving that silver elements were successfully modified on SF@PDA nanospheres.

[0052] Photothermal detection results

[0053] like Figure 4 As shown in AC, the temperature of DA solution, SF / DA solution and SF / DA / AgNO3 did not rise when irradiated with near-infrared light. Figure 4 As shown in AC, the temperature of DA solution, SF / DA solution and SF / DA / AgNO3 did not rise after near-infrared light irradiation. They were maintained at 24.4±0.7℃, 24.5±0.7℃ and 24.9±0.3℃ respectively. Figure 4 As shown in DF, the temperatures of PDA, SF@PDA and Ag@SF@PDA samples all increased after being irradiated with near-infrared light for 10 min, with PDA rising to a maximum of 53.6±0.3℃, SF@PDA rising to a maximum of 54.2±0.9℃, and Ag@SF@PDA rising to a maximum of 56.4±0.3℃.

[0054] Antibacterial performance test results of mixed solution

[0055] like Figure 5 As shown, DA solution, SF / DA solution and SF / DA / AgNO3 had no obvious antibacterial properties.

[0056] like Figure 6 As shown, the antibacterial effects of DA solution, SF / DA solution and SF / DA / AgNO3 sample after irradiation with near-infrared light for 10 min were not obvious but there was a slight effect.

[0057] Nanosphere antibacterial performance test results

[0058] like Figure 7 As shown in the figure, the antibacterial properties of PDA and SF@PDA samples are weak. The modification of silver improves the antibacterial properties of Ag@SF@PDA samples, but there are still a large number of colonies and the antibacterial rate is low.

[0059] like Figure 8 As shown in the figure, after 10 minutes of near-infrared light irradiation, the antibacterial properties of each group of samples were improved, and the photothermal effect of PDA played an antibacterial role. The Ag@SF@PDA sample had the best effect, with the survival rate of Escherichia coli and Staphylococcus aureus being 0, and the bactericidal rate reaching more than 95%. The survival rate of Escherichia coli in SF@PDA was about 14%, and the survival rate of Staphylococcus aureus was about 3%. The survival rate of Escherichia coli in PDA was about 2%, and the survival rate of Staphylococcus aureus was about 8%.

[0060] contrast Figure 5-Figure 8 It can be seen that DA solution, SF / DA solution and SF / DA / AgNO3 simply mixed have no obvious antibacterial properties. After DA is polymerized to prepare PDA nanospheres, the photothermal effect produced can effectively fight bacteria. In addition, the modification of Ag further enhances the antibacterial properties of the nanospheres, and no colonies grow.

[0061] 1. The preparation conditions of the Ag@SF@PDA of the present invention are mild and simple, and the requirements for equipment and environment are relatively low.

[0062] Second, the Ag@SF@PDA of the present invention is nanoscale and is suitable for various surfaces, such as regular and irregular surfaces, and is also suitable for different fields, such as dressings, antisepsis, tissue repair, daily cosmetics and medical treatment.

[0063] 3. The Ag@SF@PDA of the present invention has photothermal conversion performance and synergistic antibacterial performance, and can effectively kill bacteria with a sterilization rate of more than 95%.

[0064] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the scope of protection of the present invention.

Claims

1. Ag modified polydopamine composite silk fibroin nanospheres Ag@SF@PDA, characterized in that: It has a multilayer structure with PDA as the core and SF as the shell, and Ag is modified on the surface of the SF@PDA core-shell structure.

2. The method for preparing Ag-modified polydopamine composite silk fibroin nanospheres Ag@SF@PDA according to claim 1, characterized in that: The steps include: S1. Preparation of SF@PDA nanospheres Prepare SF aqueous solution, adjust the pH value to 7, disperse PDA nanospheres in the SF solution, stir and react at room temperature, then ultrasonically clean and centrifuge, and dry in low temperature vacuum to obtain SF@PDA nanospheres; S2. Preparation of Ag@SF@PDA nanospheres Silver nitrate solution and DA Tris-HCl solution were prepared, SF@PDA nanospheres were dispersed in DA Tris-HCl solution for reaction, and then silver nitrate solution was added dropwise with stirring. After the reduction reaction, they were first ultrasonically cleaned in deionized water, rinsed with deionized water, ultrasonically cleaned in ethanol, and then centrifuged and vacuum dried at room temperature to obtain Ag@SF@PDA nanospheres.

3. Use of the Ag-modified polydopamine-composite silk fibroin nanospheres Ag@SF@PDA as claimed in claim 1 as a bactericide in a dressing.

4. Use of the Ag-modified polydopamine-composite silk fibroin nanospheres Ag@SF@PDA as claimed in claim 1 as a bactericide in cosmetics.

5. A preservative, characterized in that The invention comprises the Ag-modified polydopamine composite silk fibroin nanosphere Ag@SF@PDA as described in claim 1.

Citation Information

Patent Citations

  • Preparation method of TiO2 modified dopamine antimicrobial coating

    CN106800375A

  • Organic and inorganic hybrid composite silver nanoparticle as well as preparation method and application of organic and inorganic hybrid composite silver nanoparticle

    CN109481678A

  • Method for preparing silk fibroin base bi-metal antibacterial coating

    CN112451748A

  • Biosensor based on silver@polydopamine nanosphere composite structure and preparation method

    CN113740312A